Navigating family planning: unveiling rural-urban disparities among women in India: insights from Indian demographic health survey-5 - Kaur, Manjot; Yadav, Dharmendra Kumar; Narayan, Raj; Singh, Gurdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Over the past few years, there has been an increase in the usage of family planning methods. Female sterilization remains the most commonly used method of contraception. However, there are still disparities in the use of family planning methods between urban and rural areas in India, which can be attributed to differences in education levels, cultural factors, and socio-economic factors. The study aimed to evaluate contraceptive prevalence and urban-rural disparities among married women in India. Methods: The study was based on the data collected under the National family health survey 2019-21. The NFHS-5 covered 5,12,408 currently married women (women in the age group 15-49). Descriptive and analytical analyses were used. The chi-square test and Bivariate logistic regression model were used to find the association between background characteristics and contraception use. Results: The study showed that 65.7% of the participants were using contraception, with female contraception being the most common method of contraception. The use of contraception in urban and rural settings was 67.9% and 65% respectively. Conclusions: The use of contraception has increased, with woman’s age, religion, caste, educational level, wealth index, place of residence and other factors such as total children living, total children ever born, exposure to mass media, son preference and ideal number of children being significant determinants.